Smart Biodegradable Nanoparticulate Materials: Poly-lactide-co-glycolide Functionalization with Selected Peptides - Colzani, Barbara; Biagiotti, Marco; Speranza, Giovanna; Dorati, Rossella; Modena, Tiziana; Conti, Bice; Tomasi, Corrado; Genta, Ida (Current Nanoscience, 2016)
Background: Smart nanoparticulate materials, namely tailored nanoparticles (NPs) with specific surface functionality, have recently attracted attention as useful tool for time- and site-specific drug delivery. Specifically, polymeric nanoparticles (NPs) can be chemically functionalized with different chemical entities, i.e. peptides, that selectively recognize biological substrates in vivo and target drug release. Divergent and very complex strategies can be pursued in order to obtain peptidedecorated NPs. Methods: A simple method was suggested for direct functionalization of poly-lactide-co-glicolide (PLGA) with small peptides. A solid-phase peptide synthesis was used to obtain a dodecapeptide (GE11) and a smaller tetrapeptide (FQPV). FQPV- and GE11-PLGA conjugates were obtained by optimized carbodiimide chemistry. Nanoprecipitation and solvent extraction/evaporation methods were purpose-built in order to prepare FQPV-PLGA NPs. NPs were characterized in terms of size, surface charge and adsorbed peptide amount; ex-vivo cytotoxicity studies were performed on FQPV-PLA NPs using adult fibroblasts. Results: Custom GE11, recently known as efficient Epidermal Growth Factor Receptor targeting agent, and FQPV, used as model peptide, were synthesized by solid-phase peptide synthesis achieving good purity (95%) and satisfactory process yields (70-85%). Then, FQPV- and GE11-PLGA conjugates were obtained by optimized carbodiimide chemistry achieving an high degree of functionalization (> 85%). Aware of different physico-chemical properties of peptide-PLGA conjugates with respect to plain PLGA, two different NPs preparation techniques, nanoprecipitation and solvent extraction/ evaporation methods, were purpose-built in order to prepare FQPV-PLGA NPs. Both methods revealed suitable to obtain NPs with proper dimensions for the parenteral administration (< 250nm), narrow size distribution (P.I. about 0.1), good morphological features and negative charge (about –20mV). A peptide adsorption protocol onto NPs was considered as additional strategy to increase peptide expression on NPs surface aimed at improving the targeting effectiveness. A Design of Experiment approach (DoE) has been successfully applied to the more versatile solvent extraction/ evaporation method in order to systematically highlight the influence of process parameters (organic solvent mixture, PVA concentration and polymeric solution volume) on NPs sizes. Conclusion: PLGA was successfully functionalized with two different peptides, FQPV and GE11, following the a versatile and simple carbodiimmide chemistry without further modifying polymer and/or peptide structure. Both nanoprecipitation and solvent extraction/evaporation NPs preparation methods were properly optimized in order to obtain peptide-PLGA based NPs and they can be alternatively selected according to solubility properties of both peptide-polymer conjugate and drug intended for encapsulation. Peptide adsorption on preformed PLGA NPs could be efficiently used to increase peptide expression on NPs surface thus improving cellular recognition in case of active targeting. Preliminary cytocompatibility evaluation of the selected peptide-PLGA based nanoparticulate materials shows a potential feasibility of the set-up synthetic procedures and NPs preparation methods for pharmaceutical purposes.
Keywords: peptide-PLGA conjugates